Objects in Films: Analyzing Signs - Rampazzo Gambarato, Renira (Contemporanea, 2010)
The focus of this essay is the analysis of daily objects as signs in films. Objects from everyday life acquire several functions in films: they can be solely used as scene objects or to support a particular film style. Other objects are specially chosen to translate a character’s interior state of mind or the filmmaker’s aesthetical or ethical commitment to narrative concepts. In order to understand such functions and commitments, we developed a methodology for film analysis which focuses on the objects. Object interpretation, as the starting point of film analysis, is not a new approach. For instance, French film critic André Bazin proposed that use of object interpretation in the 1950s. Similarly, German film theorist Siegfried Kracauer stated it in the 1960s. However, there is currently no existing analytical model to use when engaging in object interpretation in film. This methodology searches for the most representative objects in films which involves both quantitative and qualitative analysis; we consider the number of times each object appears in a film (quantitative analysis) as well as the context of their appearance, i.e. the type of shot used and how that creates either a larger or smaller relevance and/or expressiveness (qualitative analysis). In addition to the criteria of relevance and expressiveness, we also analyze the functionality of an object by exploring details and specifying the role various objects play in films. This research was developed at Concordia University, Montreal, Canada and was supported by the Foreign Affairs and International Trade, Canada (DFAIT).